Sanan rai wisdom in Atauro's tourism transformation. - Oliveira, Ana Carolina Ramos (Australian Journal of Anthropology, 2024)
This paper examines the history and activities of the Timorese NGO Empreza Di'ak, focusing on its role in revitalising traditional pottery (sanan rai in Tetum) on Atauro Island. Traditionally a form of women's knowledge, pottery has been reimagined in the post‐independence era as cultural heritage at risk of extinction, now transformed into commodities primarily targeting the tourist market. The paper explores the interplay of social, economic, and generational factors driving the revival of sanan rai production within the broader context of positioning Atauro as an international tourism destination. It delves into the complexities, challenges, and subjectivities that arise, alongside the unexpected situations and evolving expectations of local communities as they navigate this process of (re)engaging with and revaluing a nearly lost tradition.